Efektivitas Penggunaan Media Audio Visual Terhadap Peningkatan Hasil Belajar Siswa Dalam Pembelajaran Matematika Sekolah Dasar Kelas Tinggi - D.Yuliana Sinaga D.Yuliana Sinaga; Leni Senviani Sinaga; Santa Anderson Purba; Diah Katryn Saragih; Meliaty Sembiring; Renni Purba; Wytrisnawaty Saragih; Michael Silaen; Erik Samosir (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to explore the effectiveness of using audio-visual media in mathematics learning at the elementary school level, particularly in the upper grades. This quasi-experimental study with a pretest-posttest design involved 120 students in grades 4 and 5, who were divided into two experimental groups. Experimental group 1 used audio-visual media such as interactive videos, animations, and multimedia presentations, while experimental group 2 used conventional teaching aids.The results show that the use of audio-visual media in mathematics learning is more effective in improving student learning outcomes compared to the use of conventional teaching aids. In the pretest stage, there were no significant differences between the two groups, but after receiving different treatments, the experimental group 1 that used audio-visual media showed higher learning outcome improvements. The average posttest score in the experimental group 1 reached 76.92 with a gain value of 0.91, while the experimental group 2 only reached an average posttest score of 84.62 with a gain value of 0.89.These findings indicate that audio-visual media can transform abstract mathematical concepts into more concrete and easily understandable representations for students. The characteristics of audio-visual media that combine visual and audio elements have been proven effective in promoting conceptual understanding, increasing learning motivation, and developing students' critical thinking skills. This research contributes to the development of multimedia-based mathematics learning theory and provides innovative pedagogical practices for teachers to improve the quality of mathematics learning in elementary schools.